2020
DOI: 10.1002/curj.78
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualisations of writing in the curricula and the teachers’ guides of Greek preschool education: a critical discourse analysis

Abstract: The goal of this article is to explore the conceptualisations of writing in the curricula and the teachers’ guides of Greek preschool education (4–6 years of age). Ivanič’s framework of the six discourses of writing (the skills discourse, the creativity discourse, the process discourse, the genre discourse, the social practices discourse and the sociopolitical discourse), which shows how writing is framed in literacy education, was used for the exploration of these conceptualisations. A document‐based investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Another role of TB as a mirror of social discourse was revealed by the text-based analysis research. Critical discourse analysis of the text in TB found that TB was the representation of the discursive discourse in a particular society or culture ( Tentolouris, 2020 ), mirroring the local educators’ beliefs and knowledge about EFL education and practice ( Koljonen et al, 2018 ) and even revealing a conflict between the stated values and goals and implied messages transmitted by its language and structure features ( Lechtenberg, 2020 ). TB’s role as social discourse presenter is indicated more in local curriculum materials.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Another role of TB as a mirror of social discourse was revealed by the text-based analysis research. Critical discourse analysis of the text in TB found that TB was the representation of the discursive discourse in a particular society or culture ( Tentolouris, 2020 ), mirroring the local educators’ beliefs and knowledge about EFL education and practice ( Koljonen et al, 2018 ) and even revealing a conflict between the stated values and goals and implied messages transmitted by its language and structure features ( Lechtenberg, 2020 ). TB’s role as social discourse presenter is indicated more in local curriculum materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teacher’s Book (TB thereafter), also referred to as Teacher’s Guide (TG thereafter) ( Cox et al, 2019 ; Tentolouris, 2020 ), is an important type of curriculum resource in textbook packages. Extensive research has identified the impact of TB on teachers in which it provides curriculum resources and pedagogical support in planning and enacting teaching and scaffolds their reflection ( Koljonen et al, 2018 ; Cox et al, 2019 ; Sanchez Adorno, 2021 ).…”
Section: Introductionmentioning
confidence: 99%